IMPLEMENTATION OF EFFECTIVE CLASSROOM MANAGEMENT IN ACHIEVING LEARNING OBJECTIVES - Muhammad Habibie; Farida Asy'ari; Caroline Caroline (Adisam Publisher, 2026)
This research explores the importance of effective classroom management implementation in achieving learning objectives. Good classroom management is a fundamental factor in creating a conducive learning environment, reducing behavioural disruptions and increasing student engagement. This study highlights various strategies that teachers can use to manage the classroom more effectively, including the physical organisation of the classroom, the application of positive discipline, as well as differentiation of learning to accommodate the various needs of students. The results show that effective classroom management not only contributes to improving students' academic achievement, but also in the development of important life skills such as responsibility and self-discipline. Thus, the implementation of well-planned and thoughtful classroom management is key in supporting a more efficient learning process and the achievement of optimal educational goals.